Wound healing angiogenesis: A perspective of nurse - Alia Andriany; Takdir Tahir; Elly Lilianty Sjattar; Julianus Ake; Hasanuddin Nuru (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
-Abstract is not required - Keywords: Wound healing, Angiogenesis, Regulating Factors, Nurses, Perspectives Received: 08 January 2019; Reviewed: 19 January 2019; Received: in revised from 25 February 2019; Accepted: 28 February 2019 DOI: 10.35898/ghmj-31548